2017
DOI: 10.24832/jpnk.v2i2.588
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Media Komik Digital Akuntansi Pada Materi Menyusun Laporan Rekonsiliasi Bank Untuk Siswa SMK

Abstract: This study aimed to develop accounting digital comic media in the material of writing bank reconciliation reports for XI grade of students of vocational secondary school that is feasible to be used in the learning process. This study was a research and development refered to Borg and Gall's model, with three stages of research namely preliminary study stage, product design development and product validation. The subject of the research were students XI grade of SMK Muhammadiyah 3 Gemolong. Data collection tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 0 publications
0
15
0
9
Order By: Relevance
“…(Sukmanasa et al, 2017). As well as the development of appropriate accounting comic media based on the evaluation of material experts obtaining a score of 79%, linguists 100%, practitioners 84.64%, and limited trial 82.71% (Hidayah et al, 2017). Based on this research, it can be concluded that digital comic media is a medium that is suitable for use in learning based on the results that get an average of good and very good criteria.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…(Sukmanasa et al, 2017). As well as the development of appropriate accounting comic media based on the evaluation of material experts obtaining a score of 79%, linguists 100%, practitioners 84.64%, and limited trial 82.71% (Hidayah et al, 2017). Based on this research, it can be concluded that digital comic media is a medium that is suitable for use in learning based on the results that get an average of good and very good criteria.…”
Section: Introductionmentioning
confidence: 81%
“…The results of the assessment are very good on these aspects of media assessment. (Hidayah et al, 2017) The evaluation of material experts gets a score of 79%, linguists 100%, practitioners 84.64%, and limited trials of 82.71% based on the constituent aspects that get a very good category in each expert. Other studies are not much different.…”
Section: Discussionmentioning
confidence: 99%
“…Akan tetapi, pendidikan karakter ini belum tergambar pada proses pembelajaran di perguruan tinggi khususnya di prodi Pendidikan Bahasa Inggris STKIP PGRI Sumatera Barat. Pembelajaran adalah interaksi yang terjadi antara peserta didik dengan lingkungan belajarnya baik itu lingkungan kelas, sekolah, maupun lingkungan masyarakat (Hidayah et al, 2017). Keberhasilan sebuah proses belajar ditentukan oleh lingkungan belajarnya sehingga harus dirancang dan dikelola dengan baik dalam mengembangkan pengetahuan, keterampilan, dan sikap peserta didik.…”
Section: Pendahuluanunclassified
“…The use of this learning media can be the alternative to answer students learning needs with different characteristics. As stated by Newby, Stepich, Lehman, & Russell (Hidayah et al, 2018), multimedia is a combination of various media. In other words, multimedia is the integration of several types of media, along with different technologies, to improve the learning process.…”
Section: Ar T Ic Le In F O Abstractmentioning
confidence: 99%